Medina embolization device for the treatment of intracranial aneurysms: 18 months' angiographic results. (24th November 2018) - Haffaf, Idriss; Clarençon, Frédéric; Shotar, Eimad; Rolla-Bigliani, Claudia; Vande Perre, Saskia; Mathon, Bertrand; Drir, Mehdi; Sourour, Nader-Antoine
Abstract : Background and purpose: The Medina embolization device (MED) is a new flow disruption device combining the design of a detachable coil with an intrasaccular flow disrupter. Safety and short-term angiographic effectiveness of this device have recently been reported. However, long-term angiographic results are lacking. We report herein the 18 months' angiographic outcome in patients treated for a wide-neck intracranial aneurysm with the MED. Materials and methods: Nineteen patients (17 female, mean age 50 years) with 20 wide-neck intracranial aneurysms (six ruptured; 14 unruptured) were treated by the MED between January 2015 and June 2016. Procedure-related complications were systematically recorded; discharge and 6–9 months' follow-up modified Rankin Scale scores were assessed. Angiographic mid-term and long-term follow-up were performed with a mean delay of 6.4±1.5 months (n=16 aneurysms) and 17.7±4.2 months (n=15 aneurysms), respectively. Occlusion rates were evaluated after the procedure and at the mid-term and long-term follow-up using the Roy-Raymond scale. Results: Embolization with the MED was feasible in all except two cases (2/20, 10%). One per-procedural perforation was recorded (1/20, 5%) and one MED deployment failed because of the aneurysm's shape (1/20, 5%). Three cases of thromboembolic complications were observed (3/20, 15%). Only one thromboembolic complication was responsible for clinical sequelae. Grade A occlusion rate was 61% (11/18) after the procedure, 75% at 6 months' follow-up (12/16), and 80% (12/15) at long-term follow-up. Two cases (2/18, 11%) of recanalization at mid-term were documented angiographically. No recanalization occurred between the mid-term and long-term follow-up. Conclusion: MED is a hybrid embolization device, combining properties of a conventional coil with those of an intrasaccular flow disrupter. Our series focusing on long-term angiographic follow-up shows a satisfactory long-term occlusion rate. Larger series with longer angiographic follow-up times are warranted to confirm these preliminary results.